Comprehensive identification and distribution pattern of 37 oxygenated heterocyclic compounds in commercially important citrus juices. (December 2021) - Li, Guijie; Rouseff, Russell; Cheng, Yujiao; Zhou, Qi; Wu, Houjiu
Abstract: Oxygenated heterocyclic compounds (OHCs) are among the most biologically active components in citrus fruits which exert health benefits but also involve juice-drug interactions. However, current knowledge of OHC distribution in citrus juices is incomplete. By analyzing 173 samples from orange, mandarin, grapefruit, pomelo, lemon, and lime juices, this study constructed a comprehensive OHC (10 methoxyflavones, 12 coumarins, 15 furanocoumarins) compositional pattern of the six commercially important species. OHCs were determined using a newly developed high-resolution HPLC separation with UV and fluorescence detection. Identifications were based on matching an innovative combination of full UV and fluorescence spectra, multiwavelength fluorescence emission peak ratios, and alkyl aryl ketone retention index values with those of standards. Forty-six previously unreported OHC occurrences (12 methoxyflavones, 27 coumarins and 9 furanocoumarins) were identified in the six juice-species. Unique OHC markers were identified in mandarin (5-demethyltangeretin), pomelo (meranzin), and lime (heraclenol) juices. Orange and mandarin juices are characterized by two and five methoxyflavones respectively; pomelo and grapefruit by 5-substituted furanocoumarins and 7, 8-disubstituted coumarins; lemon and lime by byakangelicin, 8-geranyloxypsoralen, and 5-geranoxy-7-methoxycoumarin. The greatly expanded and detailed OHC distribution pattern provides additional information for future epidemiological work investigating the relationships between citrus juice OHCs intake and health outcomes. Graphical abstract: Image 1 Highlights: 50% increase of oxygen heterocyclics (OHCs) occurrences identified in citrus juices. Unique markers and characteristic OHCs identified for six important citrus juices. Bioactive OHCs' distribution offers additional health information of citrus juices.